2019
DOI: 10.1002/anie.201901668
|View full text |Cite
|
Sign up to set email alerts
|

A Coordinative Solubilizer Method to Fabricate Soft Porous Materials from Insoluble Metal–Organic Polyhedra

Abstract: Porous molecular cages have a characteristic processability arising from their solubility, which allows their incorporation into porous materials. Attaining solubility often requires covalently bound functional groups that are unnecessary for porosity and which ultimately occupy free volume in the materials, decreasing their surface areas. Here, a method is described that takes advantage of the coordination bonds in metal–organic polyhedra (MOPs) to render insoluble MOPs soluble by reversibly attaching an alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 33 publications
3
64
0
Order By: Relevance
“…[28] However, unlike most flexible MOFs and coordination polymers, which lose their porosity upon activation-triggered amorphization, amorphous RhCu-rht-MOF and both RhCu-ftw-MOFs exhibit permanent porosity. We attributed this feature to the fact that, similarly to the case of previously reported amorphous soft porous materials, [29] amorphization does not entail collapse of the Rh II -MOPs that remain accessible upon activation. Indeed, gas-sorption measurements revealed that all three MOFs are microporous to N 2 , showing BET areas (A BET ) of 700 m 2 g À1 (RhCu-rht-MOF), 400 m 2 g À1 (RhCu-ftw-MOF-1) and 680 m 2 g À1 (RhCu-ftw-MOF-2) (Figures S33,S35,36).…”
Section: Zuschriftensupporting
confidence: 66%
“…[28] However, unlike most flexible MOFs and coordination polymers, which lose their porosity upon activation-triggered amorphization, amorphous RhCu-rht-MOF and both RhCu-ftw-MOFs exhibit permanent porosity. We attributed this feature to the fact that, similarly to the case of previously reported amorphous soft porous materials, [29] amorphization does not entail collapse of the Rh II -MOPs that remain accessible upon activation. Indeed, gas-sorption measurements revealed that all three MOFs are microporous to N 2 , showing BET areas (A BET ) of 700 m 2 g À1 (RhCu-rht-MOF), 400 m 2 g À1 (RhCu-ftw-MOF-1) and 680 m 2 g À1 (RhCu-ftw-MOF-2) (Figures S33,S35,36).…”
Section: Zuschriftensupporting
confidence: 66%
“…However, unlike most flexible MOFs and coordination polymers, which lose their porosity upon activation‐triggered amorphization, amorphous RhCu‐ rht ‐MOF and both RhCu‐ ftw ‐MOFs exhibit permanent porosity. We attributed this feature to the fact that, similarly to the case of previously reported amorphous soft porous materials, [29] amorphization does not entail collapse of the Rh II ‐MOPs that remain accessible upon activation. Indeed, gas‐sorption measurements revealed that all three MOFs are microporous to N 2 , showing BET areas (A BET ) of 700 m 2 g −1 (RhCu‐ rht ‐MOF), 400 m 2 g −1 (RhCu‐ ftw ‐MOF‐1) and 680 m 2 g −1 (RhCu‐ ftw ‐MOF‐2) (Figures S33,S35,36).…”
Section: Figuresupporting
confidence: 65%
“…The monodentate ligand is replaced by a bis‐monodentate ligand during the subsequent supramolecular polymerization to form a permanently porous, amorphous polymer with superior gas uptake property compared to the covalently functionalized polymers. [ 84 ] A green pathway of liquid‐assisted grinding was attempted for the linker exchange with a water‐soluble ligand to form a fluorinated UiO‐66 analogue with higher porosity and pore volume. [ 85 ]…”
Section: Psm In Mofsmentioning
confidence: 99%